Penerapan Akad Musyarakah Pada Pemilik Alat Tromol dan Pemilik Tanah Pertambangan Emas - Agus Aditya Arisandi Saputra; Rabiatul Adawiah; Muhammad Haris (STIS DAFA MATARAM, 2023)
This research was conducted in Bungkuk Durian Village due to the presence of reserves of gold ore where there were nearly 23,227,517 tonness in South Kalimantan Provunce, one of which was in Bungkuk Durian Village, Batu Ampar District, Tanah Laut Regency. There are various ways to get the desired gold, one of which is by using a gold rock rolling tool or known as a drum tool. This research is a qualitative descriptive study using a case study approach with 6 research subjects consisiting of 2 drum equipment owners, 2 gold mining land owners and 2 subordinates or labor contractor. The research was carried out through observation, interviews, and documentation through the process of collecting data and analyzing the data with descriptive data analysis. The results of this study indicate that two groups led by the owners of drum tools where in the agreement was made verbally, before the agreement took place the parties already knew where the land was and what tools would later be used in grinding gold rock, is these collaborations the paties use cooperation contracts (musyarakah mudharabah) with different variastions or types. In addition, in the implementation of the cooperation contract there is a mistake in terms of practice where the loss should be borne jointly propotionally as long as the loss is not caused by the capital manager but what happens in the field is that the loss will only be borne by the owner of the equipment, regardless of sincerity. The owners of drum equipment because they have obtained permission from the land owner, so that this collaborative practice is categorized as syirkah fasid, namely syirkah namely one of the conditions is not fulfilled